A Clinical Report of Nonsyndromic Concomitant Hypo-Hyperdontia. (28th September 2013) - Gupta, Siddarth; Popat, Hashmat
Abstract : Although hypodontia and supernumerary teeth are often considered as mutually exclusive conditions, this case report presents an unusual case of hypodontia and a supernumerary tooth occurring simultaneously. An adolescent male was referred to the local hospital department regarding upper arch crowding. Plain film radiographs confirmed the congenital absence of both lower lateral incisors in addition to an unerupted conical supernumerary tooth in the maxillary midline. This condition has been called hypo-hyperdontia and in this paper, we discuss the clinical findings and treatment planning considerations in relation to the limited number of previously reported cases. The case report raises awareness of concomitant hypo-hyperdontia and serves to highlight that concomitant anomalies should be excluded when hypodontia or supernumerary teeth are diagnosed.